Structural Insights into Substrate Recognition by Clostridium difficile Sortase - Yin, Jui-Chieh; Fei, Chun-Hsien; Lo, Yen-Chen; Hsiao, Yu-Yuan; Chang, Jyun-Cyuan; Nix, Jay C.; Chang, Yuan-Yu; Yang, Lee-Wei; Huang, I-Hsiu; Wang, Shuying (Frontiers in Cellular and Infection Microbiology, 2016)
Sortases function as cysteine transpeptidases that catalyze the covalent attachment of virulence-associated surface proteins into the cell wall peptidoglycan in Gram-positive bacteria. The substrate proteins targeted by sortase enzymes have a cell wall sorting signal (CWSS) located at the C-terminus. Up to date, it is still not well understood how sortases with structural resemblance among different classes and diverse species of bacteria achieve substrate specificity. In this study, we focus on elucidating the molecular basis for specific recognition of peptide substrate PPKTG by Clostridium difficile sortase B (Cd-SrtB). Combining structural studies, biochemical assays and molecular dynamics simulations, we have constructed a computational model of Cd-SrtBΔN26–PPKTG complex and have validated the model by site-directed mutagensis studies and fluorescence resonance energy transfer (FRET)-based assay. Furthermore, we have revealed that the fourth amino acid in the N-terminal direction of cleavage bond (P4-Pro) of PPKTG forms specific interaction with Cd-SrtB and plays a role in configuring the peptide to allow more efficient substrate-specific cleavage by Cd-SrtB.